2001
DOI: 10.3406/lfr.2001.1024
|View full text |Cite
|
Sign up to set email alerts
|

La linguistique diachronique, les études sur la grammaticalisation et la sémantique du prototype : présentation

Abstract: Walter De Mulder: La linguistique diachronique, la grammaticalisation et la sémantique du prototype The only objective of this text is to offer a general presentation of the research on grammaticalization and of diachronic prototype semantics. After a brief reminder of the history of the studies on grammaticalization, it presents the "parameters of grammaticalization" of Lehmann. Then, it turns to the way research of grammaticalization has tried to account for the semantic evolution of the grammaticalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 3 publications
1
2
0
6
Order By: Relevance
“…This is the case for instance of determiners, with three paradigms in French and only two in almost all other Romance varieties (Carlier 2007): French has a partitive article which is absent or not completely grammaticalized elsewhere (in Lehmann's terms, the degree of grammaticalization is higher in French on account of paradigmaticity, Lehmann 1995: 123). Similar accounts can be given for demonstratives (Marchello-Nizia 2006: 178), auxiliaries and tense, aspect and modality markers (Lamiroy 1999;De Mulder 2001;De Mulder & Lamiroy 2012); this analysis could even be extended to other areas of language, such as conjunctions, prepositions and discourse markers (Fagard 2010;Fagard & Mardale 2012).…”
Section: Frenchsupporting
confidence: 54%
“…This is the case for instance of determiners, with three paradigms in French and only two in almost all other Romance varieties (Carlier 2007): French has a partitive article which is absent or not completely grammaticalized elsewhere (in Lehmann's terms, the degree of grammaticalization is higher in French on account of paradigmaticity, Lehmann 1995: 123). Similar accounts can be given for demonstratives (Marchello-Nizia 2006: 178), auxiliaries and tense, aspect and modality markers (Lamiroy 1999;De Mulder 2001;De Mulder & Lamiroy 2012); this analysis could even be extended to other areas of language, such as conjunctions, prepositions and discourse markers (Fagard 2010;Fagard & Mardale 2012).…”
Section: Frenchsupporting
confidence: 54%
“…This seems to be the case for English with respect to other Germanic languages (with Dutch not far behind, cf. König & Gast 2007), and for French vis-à-vis other Romance languages: it has been shown that French is more grammaticalized than Italian, and Italian more grammaticalized than Spanish, by comparing for instance the paradigms of determiners, auxiliaries, or the expression of tense and mood (Lamiroy 1999, 2011, Carlier 2007, De Mulder 2001. 3 The questions we address in this paper are the following: Is it really possible to compare the degree of grammaticalization of languages?…”
Section: Introductionmentioning
confidence: 99%
“…13 These elements indicate a lesser degree of grammaticalization for French regarde, with respect to its Romance counterparts. This seems to go against recent observations that French is more grammaticalized than all other Romance languages, in most if not all areas of language: from articles to quantifiers and auxiliaries (see for instance Carlier 2007, De Mulder 2001, Herslund 2005, Marchello-Nizia 2006. This apparent contradiction could be explained in one of three ways.…”
Section: Discussion: What About French?mentioning
confidence: 57%